Cellular senescence mediates the detrimental effect of prenatal dexamethasone exposure on postnatal long bone growth in mouse offspring - Jianwen Su; Yu Chai; Zhiguo Ji; Yongheng Xie; Bin Yu; Xianrong Zhang (Stem Cell Research & Therapy, 2020)
Abstract Background Prenatal dexamethasone exposure (PDE) induces low birth weight and retardation of fetal bone development which are associated with lower peak bone mass in adult offspring. Here we evaluated whether and how PDE affects postnatal long bone growth in mouse offspring. Methods Pregnant mice were injected subcutaneously with dexamethasone (1.2 mg/kg/day) every morning from gestational days (GD) 12–14. Femurs and tibias of 2-, 4-, 6-, and 12-week-old female offspring were harvested for histological, immunofluorescence, flow cytometric analysis, or microcomputed tomography (μCT) measurement. Results PDE leads to impaired bone remodeling as well as decreased bone mass in the long bone of female mouse offspring. During postnatal bone growth, significant decrease of CD45−CD29+CD105+Sca-1+ bone marrow mesenchymal stem cells (BMSCs) and CD45−Nestin+ cells, loss of type H vessels, and increment of cellular senescence were found in metaphysis of long bone in mouse offspring after PDE. We further show that eliminating the excessive senescent cells with dasatinib (5 mg/kg/day) and quercetin (50 mg/kg/day) during GD 12–14 rescues the above toxic effect of PDE on the postnatal long bone growth in female mouse offspring. Conclusion Cellular senescence mediates the toxic effect of PDE on postnatal long bone growth in mouse offspring, and inhibition of cellular senescence may be proposed for treating the retardation of bone growth caused by PDE.